Identification of Bifidobacterium strains by rRNA gene restriction patterns. - Mangin, I (1994)
Total DNA from 21 collection or industrial Bifidobacterium strains was cleaved with various restriction endonucleases. Following electrophoresis, the fragments were subjected to Southern blot hybridization with a heterologous [alpha-32P]dCTP-labeled rDNA (genes coding for rRNA) 23S gene probe. The ribosomal patterns allowed all tested strains to be differentiated and previous classifications to be confirmed. The same method was used to characterize DNA from 121 Bifidobacterium isolates collected from the intestinal flora of five human volunteers after the induction of colonic bacterial imbalance by antibiotics and absorption of a resistant exogenous Bifidobacterium strain. Hybridizations with the ribosomal probe revealed 11 different ribosomal patterns in addition to that of the exogenous strain. They permitted the Bifidobacterium populations belonging to the dominant colonic flora to be monitored over time. This experiment revealed significant and sustained alterations of the endogenous intestinal flora; indeed, some strains were eliminated, while others, probably belonging to subdominant flora, replaced them. Furthermore, even 2 months after the end of antibiotic treatment, the colonic flora remained different from that observed before treatment. Finally, our results showed that antibiotherapy did not allow colonic colonization by the exogenous strain.